2017
DOI: 10.1093/annonc/mdx156
|View full text |Cite
|
Sign up to set email alerts
|

A prospective examination of circulating tumor cell profiles in non-small-cell lung cancer molecular subgroups

Abstract: We validate that the baseline presence of ≥5 total CTCs in advanced NSCLC confers a poor prognosis. CTCs from EGFR-mutant NSCLC express epithelial-mesenchymal transition characteristics, not seen in CTCs from patients with KRAS-mutant adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 26 publications
5
93
2
Order By: Relevance
“…In total, 89.6% of the GC patients had detectable CTCs, and 54.4% of these patients had greater than 4 CTCs/7.5 mL. These levels are significantly higher than those observed with other tumor types, perhaps reflecting the high affinity for blood vessels exhibited by trophoblastic cells and the tendency of GC to metastasize through the hematogenous route . The number of CTCs is closely associated with the primary tumor size and the number of metastases, consistent with findings in non‐small‐cell lung cancer and breast cancer .…”
Section: Discussionsupporting
confidence: 79%
“…In total, 89.6% of the GC patients had detectable CTCs, and 54.4% of these patients had greater than 4 CTCs/7.5 mL. These levels are significantly higher than those observed with other tumor types, perhaps reflecting the high affinity for blood vessels exhibited by trophoblastic cells and the tendency of GC to metastasize through the hematogenous route . The number of CTCs is closely associated with the primary tumor size and the number of metastases, consistent with findings in non‐small‐cell lung cancer and breast cancer .…”
Section: Discussionsupporting
confidence: 79%
“…In the Lindsay's et al current study (10), the authors also correlated the total CTC number as well as the vim+ subgroup with the presence of EGFR, ALK and KRAS mutations. Of the patients tested for genetic aberration, 24.4% were KRAS mutated, 22.3% were EGFR mutated, and 14.4% ALK rearranged.…”
Section: Editorialmentioning
confidence: 78%
“…One of the hallmarks of EMT in tumor cells is the progressively loss of epithelial antigens, including EpCAM and cytokeratins (14), while developing mesenchymal markers, such as vimentin (15). In order to overcome this limitation in the present study, Lindsay et al took advantage of the free channel of the CellSearch platform and added a FITC-labelled anti-vimentin antibody aiming to further characterize patients' CTCs according to their vimentin expression during treatment; a patient was considered as CTC-positive if at least one vim+ cell was detected (10). Twenty-four (19.2%) patients had ≥5 CTCs/10 mL of blood and 5.6% of them were vim+.…”
Section: Editorialmentioning
confidence: 99%
“…showed the prognostic value of CTCs counted by the CellSearch system in patients with treatment-naïve stage IIIb/IV NSCLC. 49 Punnoose et al 50 reported that higher baseline CTC counts were associated with response to treatment and decreased CTC counts following treatment were associated with longer progression-free survival. The prognostic and predictive value of CTCs counted by our system will be evaluated in future clinical studies with optimization of timing of blood collection.…”
Section: Discussionmentioning
confidence: 99%